Respuesta :

Answer: f(x) = -3x + 4

Step-by-step explanation:

The function is represented by

9x + 3y= 12

This is a linear equation with x as the independent variable. This means that if x is the independent variable, the y is the dependent variable. The values of y depends on the values of x. In order to represent the function, 9x + 3y= 12, we would rearrange the function such that y stands alone on the left hand side of the equation. This becomes

9x + 3y= 12

Subtracting 9x from both sides,

9x -9x + 3y = 12 - 9x

3y = 12-9x

Dividing the lefthand side and right hand side of the equation by 3, it becomes

3y/3 = (12-9x)/3

y= -3x + 4

using function notation,

y = f(x) = -3x + 4

ACCESS MORE